Режущий инструмент с покрытием з нитрида кремния - Панов, В.С. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
Process of drawing of coverings of nitride of silicon on the hard-metal cutting tool is investigated. The optimum mode of drawing of a covering on which the experimental batch of cutters is prepared is established and tests for their firmness are conducted. On operation of turning of pigiron sleeves of cylinders of diesel engines firmness of the tool with a covering has raised in 1,7–1,8 times in comparison with a covering from carbide of the titan.